Rethinking Islamic Education in Facing the Challenges of the Twenty-first Century (American Journal of Islam and Society, 2005)
The Muslim ummah, as a world community, faces many challenges at thethreshold of the new century. The fateful event of 9/11 has revealed yetanother facet of the problems plaguing Muslim society: the existence ofradical, or what some media have labeled “militant,” Muslim groups.Despite the Muslim world’s condemnation of the 9/11 terrorist attack, theUnited States considered itself the victim and thus launched its “war againstterrorism” against the alleged perpetrators: the Taliban and al-Qaeda. Iraq,which was alleged to be building weapons of mass destruction (WMDs)and assisting al-Qaeda, became the second target. Iran would have becomethe immediate third target if the international community had supported theBush administration’s unilateral declaration of war against Iraq. But it didnot, for the allegations could not be proven.Unfortunately, this new American policy has not helped to curb aggressionor terrorism; rather, it has caused radical groups to run amok andindulge in even more acts of terrorism in Israel, Palestine, Indonesia, Turkey,Spain, Iraq, and Saudi Arabia. The 9/11 tragedy has caused the West to holdmore negative images of Muslims and Islam and has made life more difficultfor Muslims living in the West. In response, anti-Americanism hasgrown throughout the world, particularly in the Muslim world.1September 11 seemed to provide certain Muslim governments with thelicense to combat terrorism on the local front more rigorously. This actionheightened the conflicts between local Muslims and the ruling governments,as in the case of General Musharraf of Pakistan, who decided to cooperatewith Washington in its “war against terrorism” by providing bases forAmerican forces. After 9/11, Egypt, Tunisia, and Malaysia all receivedrepeated praise from Washington for their experience and seriousness incombating terrorism and joining the alliance against it, despite their trackrecord on, for example, human rights violations vis-à-vis the ruling elites’ ...